HYPERCYCLIC OPERATORS ON FREE BANACH SPACES - Загороднюк, Андрій Васильович; Марцінків, Марія Володимирівна; Можировська, Зоряна Гориславівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We consider some condition of cyclicity and hypercyclicity of operators on free Banach space over a metric spaces.